Differing Levels of Clinical Evidence: Exploring Communication Challenges in Shared Decision Making. (February 2013) - Smith, Quentin W.; Street, Richard L.; Volk, Robert J.; Fordis, Michael
The near ubiquitous access to information is transforming the roles and relationships among clinical professionals, patients, and their care givers in nearly all aspects of healthcare. Informed patients engage their physicians in conversations about their conditions, options and the tradeoffs among diagnostic and therapeutic benefits and harms. The processes of care today increasingly and explicitly integrate exploration of patient values and preferences as patients and clinicians jointly engage in reaching decisions about care. The informed patient of today who can understand and use scientific information can participate as an equal partner with her clinician. Others with beliefs or educational, cultural, or literacy backgrounds that pose challenges to comprehending and applying evidence may face disenfranchisement. These barriers are significant enough, even in the face of certainty of evidence, that clinicians and investigators have given much thought to how best to engage all patients in decision making. However, barriers remain, as most decision making must occur in settings where uncertainty, if not considerable uncertainty, accompanies any statement of what we know. In September 2011, health care and health communication experts came together in Rockville, Maryland under the auspices of the Agency for Healthcare Research and Quality (AHRQ) John M. Eisenberg Center for Clinical Decisions and Communications Science Annual Meeting to explore the challenges of differing levels of evidence in promoting shared decisions and to propose strategies for going forward in addressing these challenges. Eight scholarly papers emerged, and with this introductory article, comprise this special issue of Medical Care Research and Review .